Barriers and facilitators to discontinuing long-term use of benzodiazepine receptor agonists: a qualitative study using the Theoretical Domains Framework. (26th March 2021) - Lynch, T; Ryan, C; Cadogan, C
Abstract: Introduction: Long-term use (>3 months) of benzodiazepine receptor agonists (BZRAs) persists in healthcare settings worldwide despite guidelines recommending short-term use (≤4 weeks). Potential harms of long-term BZRA use include dependence and withdrawal symptoms. A systematic review highlighted that brief interventions targeting long-term BZRA use lacked theoretical underpinning and were often poorly described (1). It is advocated that interventions should be systematically developed and reported, use an appropriate theory-base and involve key stakeholders in their development. Semi-structured interviews based on the Theoretical Domains Framework (TDF) can be used to identify patient-level barriers and facilitators that should be targeted by interventions (2). Aim: The aim of this study was to explore the views and experiences of individuals who had previously used BZRAs on a long-term basis through semi-structured interviews and to identify key theoretical domains that acted as barriers and facilitators to discontinuing long-term BZRA use. Methods: A multi-strand convenience sampling method was used to recruit participants through community pharmacies, general practices and social media (e.g. Twitter, Instagram). Individuals who had successfully discontinued long-term BZRA use were eligible to participate if they were ≥18 years of age, community dwelling and resident in the Republic of Ireland. Individuals with a: cognitive impairment, history of epilepsy, serious mental illness (e.g. prescribed anti-psychotics) or receiving opioid substitution treatment were excluded. Semi-structured interviews were conducted using a TDF-based topic guide (2). Questions covering each TDF domain were used to explore participants' perceptions of barriers and facilitators to discontinuing long-term BZRA use. Data were recorded and transcribed verbatim. Transcripts were independently checked for accuracy. Data were analysed using the framework method. Interviews continued until data saturation was achieved. Ethical approval was granted by the RCSI Research Ethics Committee. Results: Thirteen patients were interviewed (seven female; median age: 43 years; median duration of use: six years). Key barriers to discontinuing BZRA use were identified under the 'Emotions' and 'Reinforcement' domains. These included participants' first-hand experience of withdrawal symptoms and resultant fear towards discontinuation of the medication. 'Intentions' and 'Social influences' were identified as key theoretical domains that facilitated participants in discontinuing BZRA use. For example, participants described having strong intentions to discontinue BZRA use and discussed the positive influence of healthcare professionals such as community pharmacists in supporting them. Conclusion: The study findings indicate that individuals who have successfully discontinued long-term BZRA use often have strong intentions to do so, as well as the support of healthcare professionals. However, challenges to discontinuing BZRA use include withdrawal symptoms and negative emotions towards the discontinuation process. The main strength of this study is that it used the TDF to examine barriers and facilitators to discontinuing long-term BZRA use. A notable limitation was that none of the participants were aged ≥65 years which limits the transferability of the findings. Future work will look to examine the views and experiences of current long-term BZRA users, integrate the findings with this study and map key domains to behaviour change techniques to inform the development of an intervention to reduce long-term BZRA use. References: 1. Lynch T, Ryan C, Hughes CM, Presseau J, van Allen ZM, Bradley CP, et al. Brief interventions targeting long-term benzodiazepine and Z-drug use in primary care: a systematic review and meta-analysis. Addiction. 2020;115(9):1618–39. 2. Cane J, O'Connor D, Michie S. Validation of the theoretical domains framework for use in behaviour change and implementation research. Implementation Science. 2012;7(1):37.